The Relevance of Anxiety and Mindfulness in Joe Eurell's The Shooter’s Moment of Mindfulness - Pasopati, Rommel Utungga; Camila, Myrilla Shafa; Kartiningsih, Rindrah; Wijaya, Kusuma (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This paper exposes anxiety and its coping mechanism towards mindfulness in Joe Eurell’s flash fiction entitled The Shooter’s Moment of Mindfulness. This paper employs qualitative method with closed reading as data collection technique and content analysis as data analysis technique. Through Freud’s paradigm of reality anxiety, the story is analyzed to explore the protagonist’s disturbances of mood, as well as of thinking, behavior, and physiological activities. The main character’s experiences in combat scenarios highlights how the protagonist’s mindfulness moments function as a temporary situation from the anxieties rooted in external dangers, unconscious conflicts, and moral dilemmas. In conclusion, anxiety is always temporary while mindfulness remains forever. Psychological turmoil could always be coped up with ideas and practices of prolonged mindfulness.